Fa'āliyah Tatbīq al-Wasīlah al-Filmu al-Kartūnī bī Istikhdām al-Sabbūrah al-Tafā'uliyyah lī Tarqiyyah Mahārah al-Istimā' wa al-Kalām li Ṭullāb al-Fal al-Sāmin fī al-Madrasah al-Mutawasițah al-Islāmiyyah al-Hukūmiyyah 1 Lamongan: Efektivitas Penerapan Media Film Kartun Berbasis Papan Tulis Interaktif untuk Meningkatkan Mahārah al-Istimā' dan Kalām Siswa Kelas VIII di MTsN 1 Lamongan - Bagus Nurul Kawakib; Ahmad Ghulam Zaidirrohman Al-Hakim; Muhammad Diya’ Al-Maskuri; Abdurrahman Wahid (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
Media is one component that can stimulate students' learning process to encourage the teaching and learning process. The role of the media is solely to assist teachers in teaching. This research uses quantitative research with a one-group pretest post-test experimental method, which is used to measure the effectiveness of cartoon film media using an interactive whiteboard to increase mahārah al-istimā' and kalām. The sample in this research was students in class VIII F MTs Negeri 1 Lamongan, totaling 32 students. Data collection techniques are carried out by conducting observations, interviews, tests and documentation. The results of this research indicate that the use of interactive whiteboard-based cartoon film media is quite effective in increasing the mahārah al-istimā' and kalām of class VIII F MTs Negeri 1 Lamongan students, with the mahārah al-istimā' pretest results getting a score of 55.4167 and a kalām pretest score of 52.9844 to a mahārah al-istimā' post-test of 86.1250 and a kalām post-test of 85.0125. Moreover, the results of the N-gain test show a value for mahārah al-istimā' 68.2384 and mahārah kalām 67.3120. This shows that using interactive whiteboard media based on cartoon films is quite effective in improving students' listening and speaking skills in class VIII F MTsN 1 Lamongan. Keywords: Cartoon Film, Interactive Whiteboard, Mahārah al-Istimā' and Kalām